The ribosome-associated complex RAC serves in a relay that directs nascent chains to Ssb - Zhang, Ying; Valentín Gesé, Genís; Conz, Charlotte; Lapouge, Karine; Kopp, Jürgen; Wölfle, Tina; Rospert, Sabine; Sinning, Irmgard (Nature Communications, 2020)
The ribosome-associated complex (RAC), which contains the Hsp40 protein Zuo1 and the non-canonical Hsp70 protein Ssz1 forms a chaperone triad with the fungal-specific Hsp70 protein Ssb. Here the authors combine X-ray crystallography, crosslinking and biochemical experiments and present the structure of the Zuo1 N-terminus bound to Ssz1 and demonstrate that Ssz1 is an active chaperone for nascent chains.
Gesehen am 17.04.2020